Assessment of pharmacists, public and general retailers perspectives, awareness and knowledge of registered drugs and unregistered drugs in Klang Valley / Nur Wahida Zulkifli - Zulkifli, Nur Wahida (Institute of Graduate Studies, UiTM, 2018)
The aims of this study were to explore pharmacists' perception towards the contributing factors for the existence of unregistered drugs in the market, the reasons for the public to select the unregistered drugs, to determine the association between the awareness of general retailers and the offences as well as to develop and validate a knowledge tool towards registered drugs and to identify the association with the knowledge of the public and sociodemographics. This study used the action research concept. Three types of participants were involved; pharmacist, public and general retailers and the setting around Klang Valley area. Two different semi-guided and faceto- face interviewed and purposive selection criteria were used to explore the pharmacist (n=16) and public (n=21) perception. The retrospective data (n=1441) from inspection report in Selangor was used to determine the association of awareness and offences amongst general retailers. The instrument constructed by analysing the specific literature in the area of registered drugs information in Malaysia. Then the involvement of expert panel (n=10) expertise to validate the content and public (n=10) for the reproducibility. Then, followed by the pilot test (n=T00), and continued with a final survey (n=466) by using a convenient sample. The reproducibility obtained via the intraclass correlation coefficient by using the test-retest method. Internal consistency assessed using Cronbach's alpha and construct validity used exploratory factor analysis. The thematic content analysis for both of the perceptions identified pharmacists' perception (25 themes) and publics' perception (7 themes). The majority of the pharmacists believed that low health literacy is one of the primary reasons of the contributing factors for the existence of unregistered drugs. Moreover, the majority of the public believed that the reason they select the unregistered drugs is because of the familiarity of the products and appearance of the packaging. Instead, a majority of the public who did not select the unregistered drugs believed the absence of certain characteristics of the packaging and the authorised sticker. In total, only 32.9% of general retailers were aware of registered drugs and 67.1% general retailers were not aware of registered drugs. The result showed there was an insignificant association (p=0.226) between awareness and offences. The final version of the questionnaire had 12 questions which divided into five areas of information that needed for educating the consumer on registered drugs. This questionnaire had a clarity index of 8.78 ± 0.51. The intraclass correlation coefficient was 0.96, and Cronbach's alpha, 0.866. Factor analysis revealed five factors associated with the knowledge areas. The final survey conducted and the final scores compared with the socio-demographic participants showed that age, race, the level of education and occupation significantly associated with levels of knowledge except for gender (p=0.485). This study has found that by exploring and investigating pharmacist, public and general retailers regarding these issues give a convergent answer that the main contributor of the unregistered drugs is the low level of knowledge and awareness towards registered and unregistered drugs. Thus enhancement of consumers' knowledge is one of the leading solutions that government can improve in the future.